THE ROLE OF PERSONALITY ASPECTS AND EMPLOYEE COMMITMENTS AS AM EFFORT TO MAXIMIZE WORK PERFORMANCE - Sembhodo, Abimanyu Tuwuh; Hermawati, Adya; Sodik, Sodik; Bahri, Syamsul; Syahruddin, Syahruddin; Ali, Shujahat (Jurnal Aplikasi Manajemen, 2022)
This study presents a model that links work performance, leadership behavior, personality, and work commitment. The main objective is to investigate the direct and indirect effects of personality, work commitment, and leadership behavior on work performance. The data was obtained through a questionnaire from a sample of 125 employee respondents at PT Gradion Supermarket Malang Raya. The data were analyzed by multiple regression analysis. There were seven hypotheses proved in this study. The results reveal that leadership behavior can positively contribute to employee performance. In addition, work personality also positively contributes to employee performance, work commitment positively contributes to work performance, and the work environment contributes better to leadership behavior. The results of the mediation test show that work personality has contributed well to employee work performance with the leader's behavior being implemented optimally, and work commitment is highly conditioned on employee performance by applying maximum leadership behavior. Leadership behavior has been able to make a positive contribution to the work performance of PT Gradion Supermarket employees. Employee personality makes a positive contribution to PT Gradion Supermarket employee performance. Work commitment makes a positive contribution to PT Gradion Supermarket employee performance. Personality has a positive contribution to behavior leadership.